Prevalence of Protozoal Parasites in Fish in Mosul City, Iraq (NTU Journal of Agriculture and Veterinary Science, 2024)
The current study aimed to determine the prevalence of Cryptosporidium sp, Eimeria sp., Entamoeba spp.and Giardia sp. A total of 200 pieces of five different species of fresh fish were sampled. The study was conducted from August 2023 -February 2024. Microscopic examination was done by stomach and intestine direct smears stained Lugal iodine and floatation technique. Results showed that fish were infected with Cryptosporidium sp. 26.5%, Eimeria spp. 26.5%, Entamoeba spp. 1 % and Giardia sp. 3.5% .  with no significant differences between them. As for months of the study, there were no significant infection rates where the rates ranged between 34.28% and 14.28% at p ? 0.05. Microscopically, Cryptosporidium oocysts were spheroidal to ovoidal , 4.6 - 5.5 X 3.8 - 4.7µm while Eimeria oocysts were spherical to ovoid, 12-19 µm. The cysts of Entamoeba were spherical, 10 to 18 µm. while Giardia cysts were oval with four nuclei, 8-12 ?m in size. Intestinal protozoa recorded in fish species in the current study may be due to age factor and water contamination.